The Long and Winding Road: Building Legitimacy for Complex Social Innovation in Networks1. Issue 6 (19th September 2019) - Verleye, Katrien; Perks, Helen; Gruber, Thorsten; Voets, Joris
Abstract : Social innovations, which increasingly take place in interorganizational networks, occur in environments characterized by resource scarcity. To secure access to resources, social innovators need to establish legitimacy for their initiatives. Yet, empirical work investigating the process of establishing legitimacy for social innovation—also known as legitimation—is absent. This research aims to uncover how legitimacy is established when social innovations are developed, over time, through interorganizational networks. To investigate this process, the research adopts a longitudinal case study of a network of five market‐leading organizations in the home care sector. A process‐based analysis of evidence from 33 meeting observations, 45 in‐depth interviews, and 249 documents reveals three novel findings. (1) The attainment of overall legitimacy depends on the establishment, over time, of three types of legitimacy targeted at different audiences. These are framed as building blocks oriented toward achieving interorganizational, multilevel, and external legitimacy. (2) The process of establishing legitimacy, across the building blocks, is underpinned by two dominant combinations of patterns—denoted as courting and demonstrating commitment. (3) Variation in two underlying mechanisms—conflicting tensions and role promotion—drives the enactment of these patterns across the different building blocks. The study's novelty lies in the extrication of critical types of legitimacy and dominant patterns and mechanisms which underpin the process of establishing legitimacy. It contributes to social innovation and innovation legitimation literature by providing a deep‐grained understanding of the process to establish legitimacy within social innovations carried out through interorganizational networks.